Culture of Spiny Lobster in Multi-level Floating Net Cage System Integrated with Snubnose Pompano and Abalone Shells - Junaidi, Muhammad; Diniarti, Nanda; Dwiyanti, Septiana; Diniariwisan, Damai; Sumsanto, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Modification of floating net cages (FNC) to multi-level floating net cages (MFNC) is one of the integrated cultivation options which is believed to be able to increase production capacity without increasing the horizontal area of ​​the cultivation area. Therefore, research was conducted with the aim of comparing the growth performance, survival and physiological behavior of lobsters cultivated in FNC and MFNC. The research method used was a field experiment with comparative analysis between lobster cultivation using the MFNC and FNC systems where each treatment was repeated 3 times. The parameters observed were growth performance, survival and physiological behavior of lobsters, growth and survival of snubnose pompano and abalone as well as water quality. Data analysis was carried out using the paired sample t test. The results of the research showed that there were no significant differences in the growth performance, survival and physiological behavior of lobsters reared using multi-level floating net cages and floating net cages (p > 0.05). Thus, the application of the multi-level floating net cage system in lobster cultivation is efficient in optimal use of space. Apart from that, the water quality of Ekas Bay is classified as suitable as a cultivation area for lobster, snubnose pompano and abalone, where cultivation activities using a multi-level net cage system do not have an impact on water quality, especially the parameters of temperature, pH, dissolved oxygen and salinity.